A path to true wellbeing - Abd Rahman, Shukran (Human Assistance & Development International Inc. (HADI Inc.), 2025)
Wellbeing is often associated with good health, physical strength, and daily functioning. While these are important, true wellbeing encompasses more than just the physical. It includes mental and emotional stability, meaningful social and relational connections, and spiritual grounding. Spiritual wellbeing, in particular, involves living with a clear sense of purpose, upholding core values, and nurturing a deep connection with God. When these dimensions are aligned, a person experiences not only personal balance but also inner peace. In navigating life's uncertainties and struggles, many oscillate between despair and hope. This could form some kind of emotional turmoil which often stems from individuals' intense pursuit of worldly possessions and desires. When individuals could not fulfill the goals or things they desire to achieve or own, they may fall into self-blame, overburden their thoughts, or engage in behaviours that compromise their own wellbeing and that of others. In effect, many are suffering from poor psychological health, particularly if they become too absorbed in the race to accumulate wealth.